Cognitive and language skills in adults with autism: a 40‐year follow‐up. (15th July 2013) - Howlin, Patricia; Savage, Sarah; Moss, Philippa; Tempier, Althea; Rutter, Michael
<x xml:space="preserve">Abstract</x> Background It is well established that very few individuals with autism spectrum disorders (ASD) and an IQ below 70 are able to live independently as adults. However, even amongst children with an IQ in the normal range, outcome is very variable. Childhood factors that predict later stability, improvement or decline in cognitive functioning remain uncertain and, in particular, very little is known about trajectories in later adulthood. Method Changes in cognitive and language ability from childhood to adulthood were assessed in 60 individuals with autism, all of whom had an IQ in the average range as children. Mean age in childhood = 6 years (range 2–13 years); mean age in adulthood = 44 years (range 29–64 years). Trajectories of change and factors related to current cognitive abilities were explored. Results For the majority of participants (N = 45, 75%), who were testable both as children and adults, IQ remained very stable and language also improved over time. However, 15 individuals could not be assessed on standard tests as adults and their developmental level could be estimated only on the Vineland Adaptive Behavior Scales. Almost all these adults (apart from one who had suffered a major stroke) showed severe aggressive or self‐injurious behaviours; none had ever developed language above a 3‐year level, and seven had developed epilepsy. Conclusions For most individuals with autism who had an IQ in the average range (i.e. ≥70) as children, childhood IQ proved a reliable predictor of cognitive functioning well into mid‐ to‐ later adulthood. However, a significant minority was no longer testable on standard tests as adults. Their current very low levels of functional ability were generally associated with severe behavioural disturbance and persisting and severe language impairment; 50% of these individuals had also developed epilepsy, pointing to the role of organic brain dysfunction. Implications for early intervention are discussed.